A “Gestão documental” das cartas e datas de Sesmarias do Estado do Grão Pará e Maranhão: uma perspectiva histórico-arquivística - FERREIRA, Evacy Vilhena (2022)
The objective of this work was to understand from the archival and historical point of view, the process of organization of sesmaria documents, considering that the territorial organization of the Amazon is closely related to the distribution of sesmaria letters. Methodologically, besides bibliographical research, documentary sources such as newspapers, pronouncements, correspondence, as well as interviews with public servants directly involved in the use and access of these documents in the contemporary context were used. Thus, the historical context of production of this documentation and its forms of organization within the public administration were approached, seeking to understand the political influences on this process. It was concluded that at certain times, the organization of the sesmarias date cards of Grão Pará and Maranhão approached the methods used by the contemporary archival practice, presenting, however, several gaps over time, with reflexes in its use and in access to users. As a contribution of the work, it is proposed to conduct a diplomatic analysis in a letter of sesmaria, indicating a possible way to complement the work of "management" performed. It also proposes a way to facilitate access to these documents through an index presented at the end of the paper.